INOVASI LEARNING MANAGEMENT SYSTEM (LMS) MENGGUNAKAN GOOGLE SUITE FOR EDUCATION (GSE) DALAM PEMBELAJARAN JARAK JAUH BIDANG STUDI MATEMATIKA SISWA KELAS IX DI SMP NEGERI 6 PEKALONGAN - Evi Sugiana Purnamasari; Muhammad Choirul Kamal (Delta: Jurnal Ilmiah Pendidikan Matematika, 2021)
This paper aims to determine the impact and learning outcomes of Mathematics Class IX students of SMP Negeri 6 Pekalongan in the 2020/2021 academic year on distance learning using Google Suite for Education (GSE). This paper is a best practice carried out in January-February in the even semester of the 2020/2021 school year. The object of this best practice is 32 students of class IXF at SMP Negeri 6 Pekalongan who were selected randomly (random sampling). The method used is descriptive qualitative research method. Data collection techniques in this study were interviews, observation and documentation. The best practice results show that the use of Google Suite for Education (GSE) can have a positive impact on the mathematics learning process and improve mathematics learning outcomes for class IXF students of SMP Negeri 6 Pekalongan for the 2020/2021 school year. The positive impact is seen from students' activities being more closely monitored and students being active during the learning process and the results of student activity indicators exceeding the target of 70%. The results of learning mathematics are also good, it can be seen from the results of the daily assessment of 32 students, many students who do not complete only 2 people, classical completeness is 94% and the average value is 92. So the completeness value is very high and the average value is also very high.